If that’s what she said, then that’s what she said: a usage-based, constructional analysis of pleonastic conditionals in English - Sommerer, Lotte (Corpus Pragmatics, 2023)
This paper investigates so-called pleonastic conditionals (PCs) in Present Day English, e.g. If you have to, you have to or When duty calls, duty calls. PCs are rhetorical statements in which the antecedent and the consequent are formally and semantically identical. The construction is characterized by stylistic reduplication and semantic redundancy. It is exactly this tautological nature which has a considerable effect on the discourse-pragmatic functions of the construction. The paper analyzes the construction’s frequency, form and functions by looking at data from three BYU corpora: the Movie Corpus (Davies, 2019), the TV Corpus (Davies, 2019), the Corpus of American Soap Operas (Davies, 2011). 2151 examples of if- and when-PCs are analyzed qualitatively and quantitatively. It is argued that PCs are functionally too different to be classified as default conditionals in the strict sense simply because they do not express a condition or inference. PCs are constructions used to express acceptance, indifference or certainty of the proposition. On top of that, they also code prototypicality which is a function completely overlooked in the literature so far. A Logistic Regression Model is fitted to predict the choice of the connector if or when. The statistical analysis confirms that the two types have different constructional profiles. With regards to theoretical modeling, the paper analyzes PCs from a usage-based, cognitive, construction grammar point of view and sketches the constructions’ form-meaning parings as well as their horizontal and vertical connections in the constructico